Assembly of Pyran-Fused Isoquinolines via Rhodium-Catalyzed Double Annulations of Methyl Benzimidates with Diazo Compounds - Wu, Yinsong; Zhang, Enshen; Duan, Jiahui; Xu, Keke; He, Xinwei; Shang, Yongjia (Synthesis, 2022)
A variety of pyran-fused isoquinoline derivatives were prepared in moderate to good yields through the rhodium-catalyzed dual C–H functionalization/annulation of methyl benzimidates and diazo compounds. A one-pot procedure, broad substrate scope, diversified products, and mild reaction conditions make this transformation a powerful tool for the synthesis of fused heteroarenes. In addition, the synthetic application was extended by large-scale synthesis and late-stage functionalization via Pd-catalyzed Suzuki–Miyaura, Heck, and Sonogashira cross-coupling reactions. Furthermore, a photophysical survey reveals that the pyran-fused isoquinoline products exhibit fluorescence properties and show potential for exploring fluorescent material applications.
Keywords: annulations; C–H activation; diazo compounds; isoquinolines; methyl benzimidates